Analisis Biaya Produksi Pada UMKM Kerupuk Putih Parida - Herni Herni; Wanta Wanta; Dwi Epty Hidayaty (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Cracker MSMEs, as an important sector in the Indonesian economy, often experience sudden and unpredictable increases in raw material prices. The aim of this research is to analyze production costs with the aim of increasing operating profits in the Parida white cracker business. This research uses descriptive quantitative methods. The research sample in this study was the financial records of the Parida white cracker company. The research results show that the condition of MSMEs facing rising raw material prices is currently not increasing the selling price of raw materials. Despite increases in production costs, owners may choose to absorb some or all of the increased costs to prevent customers from switching to other competitors. All costs involved must be considered, including the costs of raw materials, labor, and factory overhead. The results of this research can be a guide for MSME owners in maintaining stable production costs. Apart from that, owners are expected to have several backup suppliers so that when raw material conditions improve, MSME owners can look for suppliers who sell lower-priced products.